Deformation and Energy Absorption of Fiber Metal Laminates (FMLS) After Ballistic Impact Load - Fadly, Muhammad Syaiful; Purnowidodo, Anindito; Setyarini, Putu Hadi (SENATIK STT Adisutjipto, 2019)
Estimated damage levels from ballistic impact zones provide valuable information to make bulletproof materials more effective. This study aims to determine the impact of ballistics including deformation and energy absorption in fiber metal laminates (FMLs) that collide with 9 mm FMJ caliber bullets at speeds of 426 m/s. Finite element method modeling is done using ANSYS 18.1 workbench software. The simulation results show that FMLs can hold the bullet rate with deformation on the back of the target (DOPIII) of 8,55 mm and total energy absorption of 426,59 J at 0,000095 s. The combination of two materials, Al 5083 in the outer layer and kevlar/epoxy as the core, results in faster energy absorption and maximum stress concentrations only occur in the kevlar/epoxy so there is no damage to the first and subsequent layers.